2015
DOI: 10.1089/thy.2014.0338
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of BRAFV600E Mutation Testing Versus RAS Point Mutations and RET/PTC Rearrangements Evaluation in the Diagnosis of Thyroid Cancer

Abstract: BRAF(V600E) mutation analysis is superior to RAS point mutations and evaluation of RET/PTC rearrangements in the diagnosis of thyroid cancer, even in indeterminate lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 27 publications
3
45
1
Order By: Relevance
“…Commercially available panels include several molecular alterations known to be involved in thyroid oncogenesis, such as BRAF , Ras , RET/PTC , and paired box gene 8/peroxisome proliferator‐activated receptor γ1 ( PAX8‐PPARγ1 ). A recent study by Rossi et al demonstrated that testing for BRAF status predicted malignancy better than testing for RAS and RET/PTC and increased the sensitivity of cytology alone on indeterminate lesions . A study by Capelli and colleagues of 85 inconclusive FNA specimens (SFN/FN and suspicious diagnoses) demonstrated a positive predictive value of 100% for malignancy in the subsequent resection specimen with 100% concordance on BRAF status in the FNA and histologic samples …”
Section: Discussionmentioning
confidence: 99%
“…Commercially available panels include several molecular alterations known to be involved in thyroid oncogenesis, such as BRAF , Ras , RET/PTC , and paired box gene 8/peroxisome proliferator‐activated receptor γ1 ( PAX8‐PPARγ1 ). A recent study by Rossi et al demonstrated that testing for BRAF status predicted malignancy better than testing for RAS and RET/PTC and increased the sensitivity of cytology alone on indeterminate lesions . A study by Capelli and colleagues of 85 inconclusive FNA specimens (SFN/FN and suspicious diagnoses) demonstrated a positive predictive value of 100% for malignancy in the subsequent resection specimen with 100% concordance on BRAF status in the FNA and histologic samples …”
Section: Discussionmentioning
confidence: 99%
“…RET/PTC1 is the most common RET/PTC rearrangement and is found in up to 60-70% of PTC cases, whereas RET/PTC3 accounts for 20-30%, and other novel rearrangements for less than 5%. BRAF and RET oncogenic alterations appear to be mutually exclusive but also in this case, a recent study identified the simultaneous presence of these genes (Rossi et al, 2015).…”
Section: Ret/ptc Rearrangements:-mentioning
confidence: 61%
“…Mutation in BRAF or RAS occurs in about 70% of PTCs, suggesting that activation of the MAPK pathway is essential for the onset of carcinogenesis and that the alteration of a single effector is sufficient to cause cell transformation (Song et al, 2015). BRAF andRAS mutations are mutually exclusive (Celestino et al, 2012); however, multiple gene mutations were recently identified in several patients (Rossi et al, 2015). While RET/PTC rearrangements are particularly frequent in children (50-60%), BRAF point mutations are more common in adults than in children (50% vs 0-12%).…”
Section: Gene Mutations Associated With Thyroid Carcinomas:-mentioning
confidence: 99%
“…Clinical follow-up ranged from 2 to 10 years. Before surgery, all patients underwent US-guided FNAB and aspirates were evaluated for cytology and submitted to BRAFV600E somatic mutation analysis as previously described [25].…”
Section: Patientsmentioning
confidence: 99%